Boża sprawiedliwość objawiająca się w dziele zbawienia człowieka przez krzyż - Rakocy, Waldemar (Verbum Vitae, 2002)
The article concerns the justice of God being revealed in the act of redeeming the man by cross (on the basis of the Romans). The author first distinguishes two aspects of the justice of God: the will/decision to redeem the man and the way of carrying it out i.e. the death of the Son. Then the author puts forward Pauls two arguments for the redemption by the cross as well as questions the thesis that the Sons death puts in doubt the Fathers love. He defies the thesis of those who claim the cross was not necessary in the act of redemption. The author proves the cross had become the tool of revealing the vastness of Gods love towards the man and his justice: God chooses the action most perfect of all in reference to His creature.